2008
DOI: 10.2136/sssaj2007.0302
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Neutron Computed Tomography of Soil Water and Plant Roots

Abstract: Neutron radiography is a noninvasive imaging technique that measures the attenuation of thermal neutrons, as is done with x‐ray and γ‐ray radiography, to characterize the internal composition of materials. Neutron and x‐ray imaging are complementary techniques, with neutron imaging especially well suited for materials containing H atoms and other low‐atomic‐weight attenuating materials. Although neutron computed tomography (NCT) techniques are routinely used in engineering, relatively little is known about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 30 publications
4
44
0
Order By: Relevance
“…Nakanishi et al (2005) showed an accumulation of water in the vicinity of soybean root by using neutron tomography. A similar result was obtained by Tumlinson et al (2008) for a corn seed in sand. The authors concluded that water content gradients in the rhizosphere need further investigation.…”
Section: Introductionsupporting
confidence: 87%
“…Nakanishi et al (2005) showed an accumulation of water in the vicinity of soybean root by using neutron tomography. A similar result was obtained by Tumlinson et al (2008) for a corn seed in sand. The authors concluded that water content gradients in the rhizosphere need further investigation.…”
Section: Introductionsupporting
confidence: 87%
“…In recent years some imaging techniques have been introduced and tested for plant-soil studies, providing the possibility of measuring specific properties of the plantsoil-water system. Among the few available nondestructive methods, Neutron Radiography (NR) has increasingly allowed researchers to simultaneously image living roots and quantify soil water distribution in soil in situ (e.g., Furukawa et al 1999;Menon et al 2007;Oswald et al 2008;Tumlinson et al 2008;Moradi et al 2011;Zarebanadkouki et al 2012;Moradi et al 2013). Roots can be distinguished in neutron radiographs from soil, and soil water changes can be quantified with high spatial and temporal resolution (Moradi et al 2009;Esser et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These are usually the basis for calculation of water storage and its changes at the field scale (up to 1 km 2 ). Point measurements are scaled up to large areas applying geostatistical techniques (Western et al, 2002;Bogena et al, 2010). However, inherent small-scale soil heterogeneities and nonlinearity of processes dominate spatial and temporal variability of soil moisture and introduce sources of error that can produce significant misinterpretation of hydrological scenarios and unrealistic predictions.…”
Section: Introductionmentioning
confidence: 99%
“…At the laboratory scale, Oswald et al (2008) and Tumlinson et al (2008) presented an imaging technique (2-D and 3-D) based on a beam of low energy neutrons to investigate water redistribution and plant water uptake of a single plant in detail. Recently, using neutron transport simulations and field measurements, Zreda et al (2008) and Desilets et al (2010) introduced a new methodology of soil moisture measurements via counting natural aboveground fast neutrons, generated primarily by interactions of secondary cosmic-ray neutrons with terrestrial and atmospheric nuclei.…”
Section: Introductionmentioning
confidence: 99%